Performance of Schiff Bases Metal Complexes and their Ligand in Biological Activity: A Review - M. Ibrahim, Farah; M. Abdalhadi, Saifaldeen (Al-Nahrain Journal of Science, 2021)
Schiff bases are a broad class synthesized compound, which is prepared for the condensation process between the primary amine group and an aldehyde or ketone group. Schiff base metal complexes play an important role in many applications such as biological activity, catalytic activity, and optical property. The wide range application of Schiff base metal complexes came from the versatility of Schiff base reactions with many different transition metals. This flexibility of the reactions was given these complexes, many different properties and uses in a biological human system such as antibacterial, antifungal, anticancer, antimalarial, and others. This review gives many examples of Schiff bases, metal complexes, and there ligands with biological applications in the human system.